PHR1 involved in the regulation of low phosphate‐induced leaf senescence by modulating phosphorus homeostasis in Arabidopsis - Zhang, Jian‐Feng; Wang, You‐Yi; He, Le; Yan, Jing‐Yi; Liu, Ying‐Ying; Ruan, Zhao‐Yang; Liu, Wen‐Cheng; Yi, Long; Ren, Feng (Plant, cell and environment, 2024)
Phosphorus (P) is a crucial macronutrient for plant growth, development, and reproduction. The effects of low P (LP) stress on leaf senescence and the role of PHR1 in LP‐induced leaf senescence are still unknown. Here, we report that PHR1 plays a crucial role in LP‐induced leaf senescence, showing delayed leaf senescence in phr1 mutant and accelerated leaf senescence in 35S:PHR1 transgenic Arabidopsis under LP stress. The transcriptional profiles indicate that 763 differentially expressed SAGs (DE‐SAGs) were upregulated and 134 DE‐SAGs were downregulated by LP stress. Of the 405 DE‐SAGs regulated by PHR1, 27 DE‐SAGs were involved in P metabolism and transport. PHR1 could bind to the promoters of six DE‐SAGs (RNS1, PAP17, SAG113, NPC5, PLDζ2, and Pht1;5), and modulate them in LP‐induced senescing leaves. The analysis of RNA content, phospholipase activity, acid phosphatase activity, total P and phosphate content also revealed that PHR1 promotes P liberation from senescing leaves and transport to young tissues under LP stress. Our results indicated that PHR1 is one of the crucial modulators for P recycling and redistribution under LP stress, and the drastic decline of P level is at least one of the causes of early senescence in P‐deficient leaves. Summary Statement In Arabidopsis, PHR1 is the crucial regulator in low phosphate‐induced leaf senescence by modulating P recycling and redistribution.